Experimental work on acclimatization of chum (Oncorhynchus keta) and pink salmon (Oncorhynchus gorbuscha) in the Baltic Sea - Rimsh, E.Ya. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva, 1977)
First results of the introduction of chum and pink salmon in the Baltic Sea, peculiarities of egg incubation, rearing of the Pacific Ocean young salmon under the conditions of hatchery in Latvia are examined. Morphobiological characteristic of chum and pink salmon in the new area is presented. The terms of spawning migrations, as well as the distribution of spawners over the Soviet coastal line of the Baltic are determined. The estimation of the biological efficiency of the experimental work carried out is given. Published Not Known